Budget Institutions and Fiscal Performance in Low-Income Countries - Gollwitzer, Sophia; Kvintradze, Eteri; Prakash, Tej.; Zanna, Luis-Felipe. (Washington, D.C. : International Monetary Fund, 2010)
This paper presents, for the first time, multi-dimensional indices of the quality of budget institutions in low-income countries. The indices allow for benchmarking against the performance of middle-income countries, across regions, and according to different institutional arrangements that deliver good fiscal performance. Using the constructed indices, the paper provides preliminary empirical support for the hypotheses that strong budget institutions help improve fiscal balances and public external debt outcomes; and countries with stronger fiscal institutions have better scope to conduct countercyclical policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet